TUMBUHAN LIAR RAWA MANGROVE SEBAGAI INSEKTISIDA NABATI TERHADAP HAMA KROP KUBIS DI LAHAN RAWA PASANG SURUT - S, Asikin; Melhanah, Melhanah (AgriPeat, 2020)
Mangrove plants that usually grow on tidal swampland are very important as water storage as well as wave retention. Also, these kinds of plants are developed potentially as one source of natural insecticide. The use of botanical insecticide will reduce environmental pollution due to excessive use of chemical pesticides. The study purpose is to determine the effectiveness of extraction from several species of mangrove plants that act potentially as natural insecticides to control cabbage pests in tidal swamplands. The study was carried out using a complete randomized design, 4 treatments and 3 controls (i.e. chemical insecticides, botanical insecticide, and without insecticide), with 5 replications. The results showed that the mangrove species extract of buta-buta, bakau and jeruju as botanical insecticide was effective against cabbage crop pest, with value of average death of caterpillar in range from 86.00 to 86.67%.